2020
DOI: 10.3390/en13143750
|View full text |Cite
|
Sign up to set email alerts
|

Automated Data Filtering Approach for ANN Modeling of Distributed Energy Systems: Exploring the Application of Machine Learning

Abstract: To realize the distributed generation and to make the partnership between the dispatchable units and variable renewable resources work efficiently, accurate and flexible monitoring needs to be implemented. Due to digital transformation in the energy industry, a large amount of data is and will be captured every day, but the inability to process them in real time challenges the conventional monitoring and maintenance practices. Access to automated and reliable data-filtering tools seems to be crucial for the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Possible applications of DBSCAN are anomaly detection for aircraft trajectories [24][25][26] or fault detection of wind turbines [27]. In [28], the DBSCAN algorithm is used for identifying anomalies within engine data in order to exclude the corresponding data points from data-driven model building. One major drawback of DBSCAN is the difficulty to determine appropriate hyperparameters for multi-variate datasets [24], especially if several clusters exist with varying densities.…”
Section: Fault Detectionmentioning
confidence: 99%
“…Possible applications of DBSCAN are anomaly detection for aircraft trajectories [24][25][26] or fault detection of wind turbines [27]. In [28], the DBSCAN algorithm is used for identifying anomalies within engine data in order to exclude the corresponding data points from data-driven model building. One major drawback of DBSCAN is the difficulty to determine appropriate hyperparameters for multi-variate datasets [24], especially if several clusters exist with varying densities.…”
Section: Fault Detectionmentioning
confidence: 99%
“…A DBSCAN clustering method was proposed in [58] to detect and filter outliers. The results showed that the introduced filtering method is reliable and fast, minimizing the time and resources for data processing.…”
Section: Anomaly Detectionmentioning
confidence: 99%
“…Weizhong Yan [62] 2016 ELM Combustor anomaly detection Hui Luo and Shisheng Zhong [61] 2017 AE Improvement of anomaly detection performance Homam Nikpey Somehsaraei et al [58] 2020 ANN Enhancing model performance by filtering and detecting outliers Geunbae Lee et al [59] 2020 CAE Anomalies' identification in a monitoring system Weizhong Yan [63] 2020 ELM Enhancement of anomaly detection in a combustor Rui Xu and Weizhong Yan [64] 2020 GAN Faulty data detection Song Fu et al [60] 2021 R-DAE Anomaly detection improvement with a novel model…”
Section: Year ML Model Applicationmentioning
confidence: 99%
“…Then, DBSCAN iteratively finds the direct density-reachable and density-reachable objects from the core object. Points that do not belong to any cluster are considered outliers [26]. The key to the algorithm is how to determine MinPts and Eps adaptively.…”
Section: Dbscan Algorithmmentioning
confidence: 99%